Efficacy of systemic fungicides and antagonistic organism for the management of Phytophthora foot rot of black pepper in arecanut cropping system - Nagesh Naik, M S Lokesh, H G Hegde (Journal of Spices and Aromatic Crops, 2008)
Black pepper vines were less affected when the vines were treated either with metalaxyl goldMZ 64 WP (Ridomil gold) @ 2.5 g/vine or potassium phosphonate ( 0.5 per cent) as spray(@ 2 l-vine ) and drench twice (@ 3 l-vine) during before on set of monsoon and secondapplication in the month of August coupled with soil application of antagonistic organismi.e., Trichoderma harzianum @ 50 g (cfu 107 ) along with 1 kg of neem cake to the root zoneof the vine. Application of systemic fungicides alone i.e., metalaxyl MZ 68 WP (Ridomilgold) @ 2.5 g/vine or potassium phosphonate ( 0.5 per cent) as spray (@ 2 l-vine ) anddrench twice (@ 3 l-vine) also showed effectiveness in the combating the disease.